2014
DOI: 10.1039/c4ra10167g
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of low-temperature oxidation of CO over Pd supported on titania-coated ceria

Abstract: Pd/TiO2–CeO2 is proposed as a promising catalyst for low-temperature oxidation of CO with 100 °C lower light-off temperature than Pd/Al2O3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…in solid oxide fuel cells [3], and applications are discussed even in pharmacology due to their antioxidant properties [4]. Cerium oxides are contained as catalysts in the three-way converter for automotive exhaust control [5], they are active in the water-gas shift reaction [6,7], in the steam reforming of oxygenates [8], in soot oxidation [9], in the preferential oxidation of CO [10] and in the activation of CO 2 [11]. It has been recognized in the last two decades that thin films of oxides supported on metal surfaces provide a very useful concept as model systems for catalysis studies, allowing the controlled investigation of elementary reaction steps at the molecular level [12].…”
Section: Graphenementioning
confidence: 99%
“…in solid oxide fuel cells [3], and applications are discussed even in pharmacology due to their antioxidant properties [4]. Cerium oxides are contained as catalysts in the three-way converter for automotive exhaust control [5], they are active in the water-gas shift reaction [6,7], in the steam reforming of oxygenates [8], in soot oxidation [9], in the preferential oxidation of CO [10] and in the activation of CO 2 [11]. It has been recognized in the last two decades that thin films of oxides supported on metal surfaces provide a very useful concept as model systems for catalysis studies, allowing the controlled investigation of elementary reaction steps at the molecular level [12].…”
Section: Graphenementioning
confidence: 99%
“…Furthermore, our CuO-TiO 2 NT catalysts exhibited 100% CO conversion at a lower temperature compared to the TiO 2 -supported Au catalysts reported in the same study [54]. Moreover, comparing our catalysts to Pd catalysts supported on a CeO 2 -TiO 2 mixed oxide [55] and that supported on ZrO 2 [56] with a T 100 value close to 150 • C, the merit of the non-plasmonic CuO-TiO 2 NT catalyst with T 100 = 155 • C is notable given the comparable CO oxidation potency, lower cost, and the long-term thermal stability. …”
Section: Effect Of Cu Content On Co Oxidationmentioning
confidence: 99%
“…Compared to precious metal-based catalysts, these CuO catalysts with tuned reducibility exhibit high catalytic activity for CO oxidation and lower conversion temperatures and can be produced at lower cost of synthesis and processing. Our CuO catalysts demonstrated complete CO conversion at a temperature lower than that of CuO-supported Au catalysts 54 and those of Pd catalysts supported on a CeO 2 -TiO 2 mixed oxide 55 and on ZrO 2 . 56 Interestingly, our catalyst exhibits higher catalytic activity than pure CuO catalyst reported by Zhu et al and the activity of our catalysts is comparable to the copper-ceria catalyst reported therein.…”
mentioning
confidence: 99%